Y = ln ((x-1) / (x ^ 2 + 1))을 어떻게 구별 할 수 있습니까?

Y = ln ((x-1) / (x ^ 2 + 1))을 어떻게 구별 할 수 있습니까?
Anonim

대답:

# dy / dx = (- x ^ 2 + 2x + 1) / ((x ^ 2 + 1) (x-1)) #

설명:

# y = ln ((x-1) / (x ^ 2 + 1)) #

#y = ln (x-1) -ln (x ^ 2 + 1) #

대수의 몫 규칙 사용

지금 차별화

# dy / dx = 1 / (x-1) -1 / (x ^ 2 + 1) * d / dx (x ^ 2 + 1) #체인 규칙 사용

# dy / dx = 1 / (x-1) -1 / (x ^ 2 + 1) * 2x #

# dy / dx = 1 / (x-1) - (2x) / (x ^ 2 + 1) # lcd를 ((x-1) (x ^ 2 + 1)

(x2 + 1)) - ((2x) (x-1)) / ((x2 + 1) x-1)))) #

# dy / dx = (x ^ 2 + 1-2x ^ 2 + 2x) / ((x ^ 2 + 1) (x-1) #

# dy / dx = (- x ^ 2 + 2x + 1) / ((x ^ 2 + 1) (x-1)) #